Clinical characteristics associated with esophageal motility function. Issue 6 (June 2016) - Tanaka, Yoshimasa; Ihara, Eikichi; Nakamura, Kazuhiko; Muta, Kazumasa; Fukaura, Keita; Mukai, Koji; Bai, Xiaopeng; Takayanagi, Ryoichi
Abstract: Background and Aim: Esophageal motility disorders (EMDs) affect coordinated esophageal contractility. Recent developments in high‐resolution manometry have improved diagnosis of EMDs; however, the etiology of EMDs remains to be determined. This study aimed to determine which clinical characteristics are associated with esophageal motility. Methods: From May 2013 to July 2014, 97 patients (54 women, 43 men; age, 16–89 years) with suspected EMDs were assessed by high‐resolution manometry in Kyushu University Hospital. Esophageal motility was evaluated by measuring the distal contractile integral (DCI), basal lower esophageal sphincter pressure, and integrated relaxation pressure (IRP). Data on age, gender, body mass index (BMI), Brinkman Index, and blood tests were retrospectively collected and analyzed. Results: Fifty patients were diagnosed as normal, nine with achalasia, twelve with esophagogastric junction outflow obstruction, four with distal esophageal spasm, one with jackhammer esophagus, six with absent peristalsis, ten with frequent failed peristalsis, and five with weak peristalsis. The median DCI was 1229.0 mmHg‐s‐cm, the median basal lower esophageal sphincter pressure was 25.3 mmHg, and the median IRP was 9.6 mmHg. Patients with major motility disorders were excluded from analysis. By multivariate regression analysis, BMI ( P  = 0.029) and total cholesterol ( P  = 0.023) were negatively associated with DCI, while BMI ( P  = 0.007) was negatively associated with IRP and glucose ( P  = 0.044) was positively associated with IRP. Conclusions: Both BMI and total cholesterol could be highly predictive factors for esophageal body contractility, while BMI and glucose could be predictive factors for lower esophageal sphincter contractile function.